Knowledge, Adaptivity, and Performance in Tax Research - Magro, Anne M. (The Accounting Review, 2005)
The ability to adapt decision making to the features of decision tasks and contexts is likely an important component of professional decision making, but not all professionals will exhibit this adaptivity. One explanation for decision makers' failure to adapt when adaptivity is appropriate is that they do not possess relevant knowledge of the features of decision tasks and contexts, or institutional knowledge. In this study, I examine the relations between institutional knowledge, information search adaptivity, and performance using an experimental research design in the tax decision-making setting. The results of the study are consistent with predictions. Tax professionals with relevant institutional knowledge responded to the differential features of the taxplanning and compliance contexts by conducting broader and more extensive information search in planning than in compliance; professionals lacking institutional knowledge did not exhibit such information search adaptivity. In addition, tax research performance increased with information search adaptivity, and that adaptivity mediated the relation between institutional knowledge and tax research performance. This study extends the accounting and psychology adaptivity literatures and contributes to tax practice and education.